2013
DOI: 10.1097/ta.0b013e31828fa43d
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and mechanistic drivers of acute traumatic coagulopathy

Abstract: Background Acute Traumatic Coagulopathy (ATC) occurs after severe injury and shock and is associated with increased bleeding, morbidity and mortality. The effects of ATC and hemostatic resuscitation on outcome are not well-explored. The PRospective Observational Multicenter Major Trauma Transfusion (PROMMTT) study provided a unique opportunity to characterize coagulation and the effects of resuscitation on ATC after severe trauma. Methods Blood samples were collected upon arrival on a subset of PROMMTT patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
153
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(166 citation statements)
references
References 27 publications
5
153
1
4
Order By: Relevance
“…ATC that is caused by trauma-induced tissue injury and/or traumatic shock (generalized tissue hypoperfusion) presents as systemic activation of coagulation responses associated with increased fibrinolysis [19,26,27]. The clinical features of ATC can be summarized as follows [11,18,[28][29][30]:…”
Section: Clinical Features Of Atcmentioning
confidence: 99%
See 1 more Smart Citation
“…ATC that is caused by trauma-induced tissue injury and/or traumatic shock (generalized tissue hypoperfusion) presents as systemic activation of coagulation responses associated with increased fibrinolysis [19,26,27]. The clinical features of ATC can be summarized as follows [11,18,[28][29][30]:…”
Section: Clinical Features Of Atcmentioning
confidence: 99%
“…Pathophysiologic mechanism of increased fibrinolysis in ATC ATC presents as systemic activation of coagulation associated with increased fibrinolysis [19,26,27], and the increased fibrin(ogen)olysis is the most characteristic feature.…”
Section: Atc As Disseminated Intravascular Coagulation With a Fibrinomentioning
confidence: 99%
“…More recently, early fibrinolysis, platelet dysfunction, clotting factor inactivation and depletion, were described in acute traumatic coagulopathy [18][19][20] . To approach those multiple conditions, pharmacological agents have been incorporated in the management of coagulopathy 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, more time is allowed before undesirable pressure is applied to an initially vulnerable clot 28 . Moreover, permissive hypotension contributes to vasoconstriction and reduces dilutional effect on coagulopathy 4,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Large-volume crystalloid resuscitation can dilute coagulation factors and worsen survival. 6,46,47 Current Committee on Tactical Combat Casualty Care guidelines recommend 500 mL of Hextend (Biotime Inc.), a synthetic colloid, because of the smaller weight and volume. 48 However, studies have not confirmed efficacy in shock and have documented risk including coagulopathies.…”
Section: Discussionmentioning
confidence: 99%